2012
DOI: 10.3390/ijms13089545
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Tumor Microenvironment in Chemoresistance: Tumor-Associated Stromal Cells Protect Tumor Cells from Cell Death

Abstract: Tumor development principally occurs following the accumulation of genetic and epigenetic alterations in tumor cells. These changes pave the way for the transformation of chemosensitive cells to chemoresistant ones by influencing the uptake, metabolism, or export of drugs at the cellular level. Numerous reports have revealed the complexity of tumors and their microenvironment with tumor cells located within a heterogeneous population of stromal cells. These stromal cells (fibroblasts, endothelial or mesothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
205
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(215 citation statements)
references
References 128 publications
1
205
0
4
Order By: Relevance
“…There are recent findings that MSCs can be involved in the drug resistance development due to the release of various factors in the neighborhood of tumors [139][140][141][142][143]. Kurtova et al reported that MSCs protect chronic lymphocytic leukaemic cells from apoptosis induced by fludarabine, dexamethosone, and cyclophosphamide [125].…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 99%
“…There are recent findings that MSCs can be involved in the drug resistance development due to the release of various factors in the neighborhood of tumors [139][140][141][142][143]. Kurtova et al reported that MSCs protect chronic lymphocytic leukaemic cells from apoptosis induced by fludarabine, dexamethosone, and cyclophosphamide [125].…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 99%
“…), as well as extracellular matrix which encircle all tumor cells, and soluble factors such as growth factors, chemokines and cytokines. 61 Besides genetic and epigenetic control, cells of the TME also possess a remodelling influence on the tumor growth and its transformation from benign to malignant. For tumor propagation, cellular communication is not only required between the tumor cells but also between cancer cells and the other neighbouring cells in TME.…”
Section: Exosomes and Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…The use of two angiogenic inhibitors like VEGFR2 inhibitor and PDGFR-β together has shown very promising results in a glioma model. They target the pericytes and endothelial cells causes diminish vascular supply to the tumour [15].…”
Section: The Tumour Angiogenesismentioning
confidence: 99%
“…They interact with carcinoma cells and inflammatory cells, providing factors for reciprocal signaling loops. TAFs has been implicated to express growth factors like Epidermal Growh Factor (EGF) and transforming growth factor (TGF), Hepatocyte Growth Factor (HGF), and FGF causes carcinoma cell proliferation [15].…”
Section: Influence Of Tumour-associated Fibroblasts On Tumour Behaviourmentioning
confidence: 99%